2014
DOI: 10.1021/bi501050g
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Tau Fibrils from Minute Quantities of Seeds

Abstract: The propagation of Tau pathology in Alzheimer’s disease (AD) is thought to proceed through templated conversion of Tau protein into fibrils and cell-to-cell transfer of elongation-competent seeds. To investigate the efficiency of Tau conversion, we adapted the protein misfolding cyclic amplification assay used for the conversion of prions. Utilizing heparin as a cofactor and employing repetitive cycles of shearing and growth, synthetic Tau fibrils and Tau fibrils in AD brain extract are progressively amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 44 publications
(74 reference statements)
2
51
0
Order By: Relevance
“…32). In vitro studies on disease-associated proteins such as prion and tau showed that fragmentation of long fibrils, usually achieved by sonication, is critical for efficient seeded amplification (33,34). Moreover, it has been further demonstrated that only short tau fibrils, but not long fibrils, can be internalized and transported by neurons (35).…”
Section: Discussionmentioning
confidence: 99%
“…32). In vitro studies on disease-associated proteins such as prion and tau showed that fragmentation of long fibrils, usually achieved by sonication, is critical for efficient seeded amplification (33,34). Moreover, it has been further demonstrated that only short tau fibrils, but not long fibrils, can be internalized and transported by neurons (35).…”
Section: Discussionmentioning
confidence: 99%
“…In each case, one single or very few specific host protein(s) or peptides like Tau, a-synuclein, superoxide dismutase 1 (SOD1), Tar DNA-binding protein 43 (TDP-43), prion protein (PrP) or b-amyloid peptide (Ab) misfolds from a soluble native conformation into a harmful aggregated state, rich in beta sheets [2][3][4][5][6][7][8][9][10][11][12]. Amplification of misfolding through seeded/nucleated polymerization leads to not fully defined toxic species and neuronal destruction.…”
Section: Introductionmentioning
confidence: 99%
“…While seeding aggregation with AD brainderived PHFs has been reported in vitro for recombinant Tau (22,23), as well as in vivo (24)(25)(26), it still does not answer whether phosphorylation can drive the initial nucleation of fibers.…”
mentioning
confidence: 99%